1985
DOI: 10.1002/jlac.198519850713
|View full text |Cite
|
Sign up to set email alerts
|

Studien zur Synthese der Mitomycine, 3. Funktionalisierungen von Mitosen‐Derivaten

Abstract: Es werden Versuche zur Finführung einer (Carbamoyloxy)methyl‐Gruppe in Position 9 der Benzopyrrolizinone 1 beschrieben. Anschließend wird über eine stereoselektive Funktionalisierung der 9a‐Position und über Möglichkeiten der Einführung der Chinongruppe berichtet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Methodology described in a previous synthesis of a C9, C9a functionalized mitosane [293] was to be used to effect similar functionalization of the protected quinone 330 , however the cyclization of N -aryl succinimide 329 via Wittig olefination and subsequent Vilsmeier-Haack fromylation was the most advanced reaction reported (Scheme 65). [294] …”
Section: The Mitomycins: Synthetic Studiesmentioning
confidence: 99%
“…Methodology described in a previous synthesis of a C9, C9a functionalized mitosane [293] was to be used to effect similar functionalization of the protected quinone 330 , however the cyclization of N -aryl succinimide 329 via Wittig olefination and subsequent Vilsmeier-Haack fromylation was the most advanced reaction reported (Scheme 65). [294] …”
Section: The Mitomycins: Synthetic Studiesmentioning
confidence: 99%
“…162 In 1985, Flitsch reported that the reaction of benzopyrrolizinones with NBS in MeOH gave an unexpected side product bearing an a-tertiary ether, however the yield was only 19% (Scheme 34A). 163 Several groups have since employed these stable halogen sources to form b-halo-a-tertiary ethers. They have been effectively utilised in the synthesis of b-bromoprop-2-ynyl ethers which were applied in radical cyclisations towards high-value oxygen-containing heterocycles, for example b-methylene tetrahydrofurans (Scheme 34B).…”
Section: Halogen-mediated Alkene Difunctionalisationmentioning
confidence: 99%
“…162 In 1985, Flitsch reported that the reaction of benzopyrrolizinones with NBS in MeOH gave an unexpected side product bearing an α-tertiary ether, however the yield was only 19% (Scheme 34A). 163…”
Section: Alkene Difunctionalisationmentioning
confidence: 99%
“…Indoles are easily accessible precursors for assembling the 2-alkoxy-3-haloindolines through haloalkoxylation [28][29][30] (Chart 2a). These methods have been established to site-selective functionalization at the C2 and C3 position of indoles.…”
mentioning
confidence: 99%